2013
DOI: 10.4161/jkst.25155
|View full text |Cite
|
Sign up to set email alerts
|

LIF-STAT signaling and trophoblast biology

Abstract: Leukemia inhibitory factor (LIF) is a pleiotropic growth factor that regulates several biological functions. This review focuses on the LIF-dependent STAT activation and its impact on modulation of trophoblast functions during embryo implantation. LIF is mainly produced by the maternal endometrium at the time of implantation while its receptors are present both on the endometrium and trophoblasts. It might influence blastocyst attachment through STAT3 activation and expression of integrins. After attachment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 97 publications
1
39
0
Order By: Relevance
“…36 In our analysis, the expression of LIFR was low in the ICM. The pathway can be activated by the members of IL6 family, such as LIF and IL6.…”
Section: Discussionmentioning
confidence: 46%
“…36 In our analysis, the expression of LIFR was low in the ICM. The pathway can be activated by the members of IL6 family, such as LIF and IL6.…”
Section: Discussionmentioning
confidence: 46%
“…In a murine model of arthritis, Lif deficient mice were shown to have a reduction in clinical arthritis severity compared to wild-type disease controls (Upadhyay et al, 2012). Although LIF has been reported to be produced by fibroblasts (Suman et al, 2013), its autocrine role on IL-6 regulation following inflammatory stimulation was not previously known. In addition, other autocrine signaling involving IL-6 – IL-6R and STAT3 circuit has been described for fibroblasts (Ogura et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, new communication systems mediating the cross-talk between the blastocyst and the endometrium based on secreted miRNAs have been recently discovered in animal models. In particular, LIFdependent STAT activation and its impact on modulation of trophoblast functions during embryo implantation was described in several animal models (17)(18)(19)(20) and recently direct evidence of the role of miR-181 secreted by endometrial cells in modulating embryo implantation through the regulation of LIF has been reported in mice (21).…”
mentioning
confidence: 98%